A doutrina do Faktum da razão: um estudo da fundamentação da moral na crítica da razão prática a partir de alguns traços da história do desenvolvimento do pensamento ético de Kant - Ribeiro, Elton Cândido (2023)
This doctoral dissertation aims to investigate a frequent assertion in secondary literature, according to which the well-known doctrine of the “fact of reason”, present in the Critique of Practical Reason, would be a novelty in the framework of Kantian thought, arising after difficulties with the deduction of the categorical imperative in the Third Section of the Groundwork for the Metaphysics of Morals. More specifically, the dissertation asks whether it might not be the case that the assertion of the independence of the practical from the theoretical standpoint was already present in the pre-critical period, so that Kant, in presenting the doctrine of the Faktum in the second Critique, was in fact reaffirming a familiar thesis. To investigate this question, the dissertation is structured in four chapters. The first one presents the status quaestionis of the doctrine of the fact of reason in the secondary literature. The second and third chapters, meanwhile, proceed historically, examining the Kantian ethical documents of the first half of the 1760s and of the second half, as well as those of the so-called “silent decade”. The final chapter discusses the results found, confronting some common objections that frequently link Kant’s ethics in an essential way to his new standpoint in theoretical metaphysics